2020
DOI: 10.7717/peerj.8404
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of NADPH oxidase genes in response to ABA and abiotic stresses, and in fibre formation in Gossypium

Abstract: Plasma membrane NADPH oxidases, also named respiratory burst oxidase homologues (Rbohs), play pivotal roles in many aspects of growth and development, as well as in responses to hormone signalings and various biotic and abiotic stresses. Although Rbohs family members have been identified in several plants, little is known about Rbohs in Gossypium. In this report, we characterized 13, 13, 26 and 19 Rbohs in G. arboretum, G. raimondii, G. hirsutum and G. barbadense, respectively. These Rbohs were conservative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We systematically identified 87 Rboh genes in these representative five sequenced Gossypium species: G. arboretum, G. raimondii, G. australe, G. hirsutum, and G. barbadense. Both G. arboretum and G. raimondii harbored 13 Rboh genes, a result that agrees with the findings of Zhang et al (2020). The main difference with that work is that we found 24 and 27 Rboh genes in G. hirsutum and G. barbadense, while they found 26 and 19, respectively (Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…We systematically identified 87 Rboh genes in these representative five sequenced Gossypium species: G. arboretum, G. raimondii, G. australe, G. hirsutum, and G. barbadense. Both G. arboretum and G. raimondii harbored 13 Rboh genes, a result that agrees with the findings of Zhang et al (2020). The main difference with that work is that we found 24 and 27 Rboh genes in G. hirsutum and G. barbadense, while they found 26 and 19, respectively (Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown that shoot ABA application promotes root growth by accelerating both cell division and elongation of the root tips ( Lin and Kao, 2001 ). ABA synthesis regulates fiber development ( Zhang G. et al, 2020 ). Therefore, we chose GH_D12G1806 as our candidate genes for the next step of functional verification.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are many studies focus on the response of circadian clock to abiotic stress in crops ( Flowers, 2004 ; Lu et al, 2017 ; Zhang et al, 2020 ). TOC1 can bind to the ABAR promoter of ABA-related genes and regulate its circadian rhythm expression, and can be thought to act as molecular switches between drought stress signaling pathways and circadian clocks in Arabidopsis ( Legnaioli, Cuevas & Mas, 2009 ).…”
Section: Discussionmentioning
confidence: 99%